(3GdeYVdI GdCefjI aj GdfXGe GdOhdj heSJbHd GdJhGRf GdGSJQGJjLj GdYGdej (B/s - (3GdHcQj, eGRf MejOs ((3YeGf, GdCQOf (B:s (3OGQ CeLO ddfTQ hGdJhRjY WHGYI(B. (3fTQ(B. (3JhRjY ;s [(3ecGf GdfTQ ZjQ eMOO(B] :s (3EHUGQ fGTQhf hehRYhf (B:s (3OGQ caGAI GdeYQaI WHGYI(B. (3fTQ(B. (3JhRjY,s, 2023)
(3jJfGhd gPG GdcJGH hHQDjI TGedI ehVhYI GdeYVdI GdCefjI HGYJHGQgG eQJcR eMhQj aj ChdhjGJ GdOhd hHeNJda eSJhjGJgG hKbdgG GdEbdjej Ch GdOhdj, aVdG Yf gjcdjI GdfXGe GdOhdj GdPj jYO GdfSb deLed GdJaGYdGJ aj GdHjFI GdOhdjI hef NdGd GdahGYd GdJj JeJdc GdhSGFd hGdCOhGJ dJMbjb CgOGagG heUGdMgG GdYdjG , ceG jVY GdcJGH eSGQGJ Objbjg deSJbHd GdJhGRfGJ GdYGdejI hef efWdb GdbhI hGdbOQGJ hBdjGJ GdJhXja ddbhi GdYXei hGdcHQi haj ebOeJgG GdhdGjGJ GdeJMOI GdCeQjcjI hGdUjf hQhSjG GdGJMGOjI GdJj JTcd eKdK Gdbhi GdGSJQGJjLj GdYGdej hdGSjeG Cf gPg Gdbhi JSYi dJYXje bhJgG hGdMaGX YdjgG hEMGWI GdeYVdI GdCefjI hJbhjV aLhGJ GNJdGd GdCef GdOhdj hUhdG dMGdI ef GdGSJbQGQ GdfSHj aj GdHjFI GdOhdjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B437-460.s
Keywords: (3GdSjGSI GdOhdjIs; (3GdJhGRf GdSjGSjs; (3GdCef GdOhdjs; (3GdefXeGJ GdOhdjIs